Calculus II For Dummies - Zegarelli, Mark (For Dummies, 2023)
The easy (okay, easier) way to master advanced calculus topics and theories Calculus II For Dummies will help you get through your (notoriously difficult) calc class--or pass a standardized test like the MCAT with flying colors. Calculus is required for many majors, but not everyone's a natural at it. This friendly book breaks down tricky concepts in plain English, in a way that you can understand. Practical examples and detailed walkthroughs help you manage differentiation, integration, and everything in between. You'll refresh your knowledge of algebra, pre-calc and Calculus I topics, then move on to the more advanced stuff, with plenty of problem-solving tips along the way. Review Algebra, Pre-Calculus, and Calculus I concepts Make sense of complicated processes and equations Get clear explanations of how to use trigonometry functions Walk through practice examples to master Calc II Use this essential resource as a supplement to your textbook or as refresher before taking a test--it's packed with all the helpful knowledge you need to succeed in Calculus II.